Inotuzumab ozogamicin in B-cell precursor acute lymphoblastic leukemia: efficacy, toxicity, and practical considerations - Rubinstein, Jeremy D.; O’Brien, Maureen M. (Frontiers in Immunology, 2023)
Inotuzumab ozogamicin (InO) is an antibody drug conjugate composed of a humanized monoclonal antibody targeting the cell surface receptor CD22 coupled to a cytotoxic calicheamicin payload via an acid labile linker. InO has shown significant activity in relapsed and refractory B-cell precursor acute lymphoblastic leukemia (BCP-ALL) in both single agent and combination chemotherapy regimens in adult and pediatric trials. Its use in newly diagnosed elderly patients has also been established while clinical trials investigating its use in newly diagnosed pediatric patients and fit adults are ongoing. Notable toxicities include sinusoidal obstruction syndrome (SOS), particularly in patients who undergo hematopoietic stem cell transplantation (HSCT) after InO as well as myelosuppression and B-cell aplasia which confer increased infection risk, particularly in combination with cytotoxic chemotherapy. In the relapsed/refractory (R/R) setting, the planned subsequent curative therapy modality must be considered when using InO to mitigate SOS risk if proceeding to HSCT and account for potential B-cell aplasia if proceeding to chimeric antigen receptor CAR-T therapy. Studies exploring mechanisms of resistance or failure of InO are ongoing but modulation or loss CD22 expression, alternative CD22 splicing, and high Bcl-2 expression have been implicated. In this review, we will summarize the currently available data on InO, with an emphasis on pediatric trials, and explore future directions including combinatorial therapy.